2021
DOI: 10.1088/1674-1056/ac05a4
|View full text |Cite
|
Sign up to set email alerts
|

Large-area fabrication: The next target of perovskite light-emitting diodes*

Abstract: Perovskite materials show exciting potential for light-emitting diodes (LEDs) owing to their intrinsically high photoluminescence efficiency and color purity. The research focusing on perovskite light-emitting diodes (PeLEDs) has experienced an exponential growth in the past six years. The maximum external quantum efficiency of red, green, and blue PeLEDs has surpassed 20%, 20%, and 10%, respectively. Nevertheless, the current PeLEDs are still in the laboratory stage, and the key for further development of PeL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Ziming Chen 1 , Robert L Z Hoye 1,2 and Hin-Lap Yip 3 1 Imperial College London, United Kingdom 2 University of Oxford, United Kingdom 3 City University of Hong Kong, Hong Kong Special Administrative Region of China, People's Republic of China Over the past 9 years, metal-halide perovskites, with their excellent optoelectronic properties and compatibility with low-capital fabrication methods, have successfully joined the solid-state emitter family [1]. Perovskite light-emitting diodes (PeLEDs) share many similarities with organic LEDs (OLEDs), including processability with solution-and vapor-based techniques, as well as compatibility with flexible polymer/paper substrates and printing techniques for large-scale fabrication or micro-patterning [2][3][4][5][6][7]. But a critical advantage of PeLEDs over OLEDs is their much narrower emission peaks (both in photoluminescence (PL) and electroluminescence (EL)) and high color purity across the entire visible and near-infrared wavelength ranges [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziming Chen 1 , Robert L Z Hoye 1,2 and Hin-Lap Yip 3 1 Imperial College London, United Kingdom 2 University of Oxford, United Kingdom 3 City University of Hong Kong, Hong Kong Special Administrative Region of China, People's Republic of China Over the past 9 years, metal-halide perovskites, with their excellent optoelectronic properties and compatibility with low-capital fabrication methods, have successfully joined the solid-state emitter family [1]. Perovskite light-emitting diodes (PeLEDs) share many similarities with organic LEDs (OLEDs), including processability with solution-and vapor-based techniques, as well as compatibility with flexible polymer/paper substrates and printing techniques for large-scale fabrication or micro-patterning [2][3][4][5][6][7]. But a critical advantage of PeLEDs over OLEDs is their much narrower emission peaks (both in photoluminescence (PL) and electroluminescence (EL)) and high color purity across the entire visible and near-infrared wavelength ranges [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the PeLED device section (sections [3][4][5][6][7][8][9][10][11][12], we propose a standard measuring method for PeLEDs that will help institutionalize the reported EQEs in the field. Then large-scale and vacuum-deposited PeLEDs are demonstrated to exemplify the feature of solution processing and the compatibility with the industrial film deposition process, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Halide lead perovskite CsPbX 3 (X=Br, Cl, I) quantum dots (QDs) have emerged as a promising class of semiconductor materials. Owing to their excellent long-term stability, high electron mobility [1,2], narrow emission linewidth [3], and high quantum yields [4], CsPbX 3 QDs have become promising candidates for application in light-emitting diodes (LEDs) [5,6] , photoluminescence materials [7][8][9], and optoelectronic devices [10,11]. Recently, it has been widely reported that CsPbBr 3 QDs (photoactive materials) can be combined with other metal oxide semiconductor materials to form heterojunction [12][13][14].…”
Section: Introductionmentioning
confidence: 99%